Plasma Etching of SiO2 Contact Holes Using Hexafluoroisopropanol and C4F8 - You, Sanghyun; Lee, Yu Jong; Chae, Heeyeop; Kim, Chang Koo (Coatings, 2022)
This study presents the feasibility of the use of hexafluoroisopropanol (HFIP) as a substitute to perfluorocarbon (PFC) for the plasma etching of SiO2 to confront the continuous increase in demand for PFC emission reduction. SiO2 etching is conducted in HFIP/Ar and C4F8/Ar plasmas, respectively, and its characteristics are compared. The SiO2 etch rates in the HFIP/Ar plasma are higher compared with those in the C4F8/Ar plasma. The thickness of the steady-state fluorocarbon films formed on the surface of SiO2 are lower in the HFIP/Ar plasma compared with in the C4F8/Ar plasma. Higher SiO2 etch rates and thinner fluorocarbon films in the HFIP/Ar plasma are attributed to the oxygen atoms in HFIP, which generate oxygen radicals that react with the fluorocarbon films to turn into volatile products. Due to the higher dissociation of C-F bonds in CF4 compared with in HFIP, the etch rates of SiO2 in the C4F8/Ar plasma increase more rapidly with the magnitude of the bias voltage compared with those in the HFIP/Ar plasma. The etch profiles of the 200 nm diameter SiO2 contact holes with an aspect ratio of 12 show that fairly anisotropic SiO2 contact hole etching was achieved successfully using the HFIP/Ar plasma.
Keywords: contact holes; etch profile; hexafluoroisopropanol; perfluorocarbon; plasma etching